2006
DOI: 10.1590/s1415-47572006000200030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in geographical populations of Aedes aegypti (Diptera, Culicidae) in Brazil elucidated by molecular markers

Abstract: The tropical mosquito, Aedes aegypti is the most important domestic vector of urban yellow fever and dengue. Genetic population studies on this vector are important because they may lead to new tools for surveillance. An analysis of genetic structure was conducted among populations of A. aegypti from 11 localities in four demographic regions within six Brazilian federal states. Markers included 21 random amplified polymorphic DNA (RAPD) loci. RAPD markers were detected among populations and cluster analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 18 publications
4
27
0
2
Order By: Relevance
“…Values of expected H were similar to those found previously by de Sousa et al (2001) in several Argentine cities using only 17 RAPD loci. Likewise, levels of variability were similar to those found in other populations from Brazil (Ayres et al 2003, Paduan et al 2006), Puerto Rico (Apostol et al 1996) and Mexico (Gorrochotegui-Escalante et al 2000), using the same molecular markers. Rondán Dueñas (2005) reported that haplotype diversity values at the mitochondrial control region in Ae.…”
Section: Discussionsupporting
confidence: 83%
“…Values of expected H were similar to those found previously by de Sousa et al (2001) in several Argentine cities using only 17 RAPD loci. Likewise, levels of variability were similar to those found in other populations from Brazil (Ayres et al 2003, Paduan et al 2006), Puerto Rico (Apostol et al 1996) and Mexico (Gorrochotegui-Escalante et al 2000), using the same molecular markers. Rondán Dueñas (2005) reported that haplotype diversity values at the mitochondrial control region in Ae.…”
Section: Discussionsupporting
confidence: 83%
“…The dispersal due to transportation, indiscriminate use of insecticide and the elimination of natural and artificial breeding places had a significant effect on migration, genetic exchange and the genetic structure of mosquitoes (Paupy et al, 2000;Lerdthusnee and Chareonviriyaphap, 2002). The genetic diversity in mosquito populations had been widely reported to exist and inferred through various molecular techniques (Franco et al, 2002;Paduan et al, 2006). Subsequent molecular studies have been conducted for mosquitoes in developed countries and being applied to control diseases spread by mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…3). Paduan et al (2006) described a low genetic variation (GST = 0.208) with a higher degree of gene flow (Nm = 1.90). Similarly, the current study showed a genetic variation (GST = 0.113) with a high gene flow (Nm =4.014) in urban area; whereas population differentiation (GST = 0.134) with a moderate gene flow (Nm =2.62) found in rural area indicated low intra-and inter-population genetic variability in mosquito populations.…”
Section: Discussionmentioning
confidence: 99%
“…The geographic locations of the Brazilian populations are shown on a map in Figure 1. The analyzed mosquitoes were the F1 generation of the collected individuals, except for the RO population, which has been maintained in laboratory for at least 25 years (Paduan et al, 2006). Three of the samples (RO, SL and BA) were furnished by the Superintendence of Endemic Disease Control (SUCEN), located at Marilia in São Paulo State, Brazil, which also performed the tests to classify the five populations as resistant, susceptible or having an intermediate status designated "decreased susceptibility".…”
Section: Mosquitoesmentioning
confidence: 99%